The European Social Fund and Popularizing Lifelong Learning and Vocational Education in the Lubelskie Voivodship - Grabczuk, Krzysztof (Regional Barometer. Analyses & Prognoses, 2012)
The accession of Poland to the European Union created both new opportunities and tasks for many entities. This article presents the analysis of the use of the European funds from the European Social Fund for vocational education (9.2 Improvement of the quality and attractiveness of vocational training) and lifelong learning (9.3 Popularizing formal lifelong learning in school forms). These two measures have been selected by the author because expending these funds on the above mentioned tasks in the current financial perspective of 2007–2012 is one of the most difficult. The SWOT analysis conducted in Poland 2006, i.e. just after implementing the Operational Programme of the European Social Fund, indicated the following: (1) low quality and attractiveness of vocational education system, (2) low popularity of cooperation between employers and schools, (3) weak system of educational-vocational consultancy, (4) weak connections between curriculums and labour market, and (5) low rate of participation of adults in lifelong learning. According to numerous researches, the vocational educational system is at a much lower level than the general education system, and therefore there is not so much interest in it. On the other hand, there is a big demand for graduates of vocational schools on the labour market. The European funds are a chance to improve the quality and attractiveness of vocational education and its promotion. It is also a chance to introduce innovative forms of teaching, equip schools with modern didactic materials, and provide additional entrepreneurship and foreign languages classes. In a modern market economy and with an incredibly fast rate of civilization development, society has to permanently upgrade qualifications and skills to catch up with changing technologies. The modern knowledge-based economy and technological race mean that employers need employees who are better educated. Their knowledge, skills and creativity will have a significant influence on the competitiveness of companies, regions and states.